Slave to the Rhythm: The Problem of Creative Pedagogy and the Teaching of Creativity. - Russell, Francis (Deleuze Studies, 2015)
Since the mid-twentieth century the concepts 'creativity' and 'innovation' have become increasingly significant within a host of fields, such as education, medicine, engineering, technology and science. Moreover, such terms appear to have become ubiquitous, if not hegemonic, within the contemporary discourses that inform debates that surround the allocation and cultivation of the social capital that is native to education, both tertiary and otherwise. Given that the thinking of creativity appears increasingly to be possible only within the contemporary logics of utility and productivity that inform the discussion of the 'knowledge economy', the philosophical works of Gilles Deleuze are perhaps now more vital than ever, at least insofar as he is able to provide the possibility of approaching an 'otherwise' to the contemporary thinking of 'creativity'. This paper discusses the possibility for Deleuze's discussion of rhythm - as can be located in his text A Thousand Plateaus and his work on the twentieth-century painter Francis Bacon - as providing the means for better posing the question of the conditions for the emergence of a fundamentally creative approach to teaching creativity to be conceptualized within our present situation.